Loop extrusion: theory meets single-molecule experiments. (June 2020) - Banigan, Edward J.; Mirny, Leonid A.
Abstract: Chromosomes are organized as chromatin loops that promote segregation, enhancer-promoter interactions, and other genomic functions. Loops were hypothesized to form by 'loop extrusion, ' by which structural maintenance of chromosomes (SMC) complexes, such as condensin and cohesin, bind to chromatin, reel it in, and extrude it as a loop. However, such exotic motor activity had never been observed. Following an explosion of indirect evidence, recent single-molecule experiments directly imaged DNA loop extrusion by condensin and cohesin in vitro . These experiments observe rapid (kb/s) extrusion that requires ATP hydrolysis and stalls under pN forces. Surprisingly, condensin extrudes loops asymmetrically, challenging previous models. Extrusion by cohesin is symmetric but requires the protein Nipbl. We discuss how SMC complexes may perform their functions on chromatin in vivo .